Early age evolution of rheological properties of over-stabilized bitumen emulsion-cement pastes. (30th October 2016) - Garilli, Erika; Autelitano, Federico; Godenzoni, Carlotta; Graziani, Andrea; Giuliani, Felice
Highlights: Over-stabilized bitumen emulsion delays the final setting time of BEC pastes. Early age viscosity of BEC pastes is related to the concentration of dispersed phases. At low concentration, viscosity evolution of BEC depends on the emulsifier content. At high concentration, viscosity evolution of BEC depends on the concentration itself. Abstract: This paper focuses on the early age evolution of consistency and rheological properties of fresh bitumen emulsion-cement (BEC) pastes. The tested BEC pastes were fabricated using a Portland limestone cement and an over-stabilized bitumen emulsion and were characterized by water to cement ratio ranging between 0.33 and 1 and by bitumen to cement ratio ranging between 0 and 1. The testing plan included the measurement of sedimentation tendency, setting time and evolution of viscosity with increasing storage time. Rheological measurements were also carried out on bitumen emulsion-filler mastics prepared with a reference filler. Results showed that, regardless of water content, the initial and final setting time of BEC pastes increased when the proportion of bitumen with respect to cement was increased. When the total concentration of the dispersed phases was low, the increase in bitumen concentration with respect to cement led to a reduction in the rate of viscosity increase with storage time; on the other hand, when the total concentration of the dispersed phases was high the increase of storage time led to a change in the physical state of the pastes (from fluid to plastic) due to coalescence of bitumen droplets.